Analysis of Inhibiting Factors for QRIS Adoption in the Digitalization of MSMEs in East Jakarta - Alviandi Agustin; Oky Irnawati (Department of Informatics Engineering, 2026)
The Quick Response Code Indonesian Standard (QRIS) was introduced by Bank Indonesia to unify QR-based payments and accelerate the digitalization of Micro, Small, and Medium Enterprises (MSMEs). However, its adoption among MSMEs in East Jakarta remains suboptimal. This study aims to analyze the inhibiting factors affecting QRIS adoption by applying the Unified Theory of Acceptance and Use of Technology (UTAUT), extended with the perceived risk construct. A quantitative approach was employed using purposive sampling of 100 MSME respondents. Data were collected through a structured questionnaire consisting of 13 items and analyzed using descriptive statistics and Spearman’s rank correlation. The results show that social influence is the most dominant inhibiting factor, while perceived risk also contributes but to a lesser extent. Conversely, facilitating conditions, effort expectancy, and performance expectancy are relatively favorable. Correlation analysis indicates that effort expectancy plays a central role, as it is strongly associated with other constructs. These findings suggest that improving digital literacy, strengthening awareness campaigns, and enhancing trust in digital transactions are necessary to accelerate QRIS adoption among MSMEs in East Jakarta. Future research may include moderating variables such as trust and policy support to provide deeper insights into long-term adoption behavior.